Advances in the identification of candidate genes for selection of cattle for ribeye area: a systematic review - Rocha-Silva, Mérik; Rocha Sarmento, Jo´se Lindenberg; Silva Sena, Luciano (Scientia Agraria Paranaensis, 2024)
In this systematic review, we aimed to clarify which genes or genomic regions influence the development of the longissimus dorsi muscle in cattle. An integrative review was performed based on quantitative and qualitative data published on PubMed, using the search criteria “ribeye area and carcass and taurus”. We verified significant influence of the breed origin, so that, provided environmental effects that benefit the formation of muscle tissues, with the proportional allometric growth, the fat deposition will not be affected; however, there are nutritional limitations for the development of all tissues in commercial livestock production systems. The diversity of genes and SNPs associated with loin eye area (REA) allow the conduction of investigations within breed, associating REA with traits of economic importance that are difficult to measure, such as those related to reproduction. The processes associated with the expression of the genes reported in this review represent a frontier that will be crossed by the omics sciences.